Intra-tumoral molecular heterogeneity of grade 3 astrocytomas and oligodendrogliomas and its significance in disease prognosis - P. V. Nikitin; A. Yu. Belyaev; G. R. Musina; G. L. Kobyakov; I. N. Pronin; D. Yu. Usachev (Опухоли головы и шеи, 2023)
Introduction. Malignant brain tumors, such as anaplastic astrocytomas and anaplastic oligodendrogliomas grade 3, are characterized by high aggressiveness and pose a serious clinical problem. This study focuses on assessing intratumoral heterogeneity in anaplastic astrocytomas and anaplastic oligodendrogliomas and its impact on disease prognosis.Aim. To study characteristics of intratumoral heterogeneity, in particular such morphological criteria as necrosis, vascular proliferation, mitoses, and mutations in the most significant for glioma progression genes in the groups of grade III astrocytomas and oligodendrogliomas, as well as analysis of prognostic significance of these parameters.Materials and methods. The study included 389 patients with IDH-mutant astrocytomas and 200 patients with oligodendrogliomas. The mean Ki-67 labeling index of astrocytomas was 12.78 %, while that of oligodendrogliomas was 8.54 %.Results. The presence of vascular proliferation, necrosis, of more than 20 % of the area of the specimen occupied by sarcomatous-like areas and the number of mitoses significantly affected not only disease-free survival but also overall survival of patients. In the clinical setting, mutations in the TERT promoter gene, amplification and mutation of the EGFR gene, deletion of the CDKN2A gene, and TP53 gene had a significant negative impact on recurrence-free and overall survival.Conclusion. The results of single-cell RNA sequencing showed additional factors, including sarcomatous-like areas, as well as TERT, EGFR, CDKN2A and TP53 mutations, in the progression of the tumors under consideration and in ensuring an increase in their malignant potential.